Engineering Multi-Agent Systems : Third International Workshop, EMAS 2015, Istanbul, Turkey, May 5, 2015, Revised, Selected, and Invited Papers - Baldoni, Matteo; Baresi, Luciano; Dastani, Mehdi; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the Third International Workshop on Engineering Multi-Agent Systems, EMAS 2015, held in Istanbul, Turkey, in May 2015. The 10 full papers, presented with two invited talks, were carefully reviewed and selected from 19 submissions. The focus of the papers is on the topics such as: programming frameworks, languages, models and abstractions for MAS; formal methods and declarative technologies for specification, verification and engineering of MAS; MAS software engineering methodologies and techniques, and development concerns; interoperability and integration; tools and testbeds; MAS techniques; and empirical studies and (industrial) experience reports.
Programming frameworks -- Languages, models and abstractions for MAS -- Formal methods and declarative technologies for specification, verification and engineering of MAS -- MAS software engineering methodologies and techniques, and development concerns -- Interoperability and integration -- Tools and testbeds -- MAS techniques -- Empirical studies and (industrial) experience reports.
Keywords: Artificial intelligence; Software engineering; Computer science; Artificial Intelligence; Software Engineering; Programming Techniques